16.8. dhsjdjdjdjdjdjdjdhd
Step-by-step explanation:
The sum of ages of two friends is 13 years.
The product of their ages is 42.
<em>Let the age of 1st friend and 2nd friend is x, y respectively.</em>
<em>1 st condition= The sum of ages of two friends is 13 y</em><em>r</em><em>s. </em>
i.e x+y = 13........ (I)
<em>2nd condition= The product of their ages is 42.</em>
i.e X*y = 42........(ii)
From equation (I)
X+y = 13
or, X = 13-y........ (iii)
<em>Putting the equation (iii) in equation (ii).</em>
X*y= 42
(13-y) * y = 42
13y - y^2 = 42
![{y}^{2} - 13y + 42 = 0](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20-%2013y%20%2B%2042%20%3D%200)
![{y}^{2} - (7 + 6)y + 42= 0](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20%20-%20%287%20%2B%206%29y%20%2B%2042%3D%200)
![{y}^{2} - 7y - 6y + 42 = 0](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20-%207y%20-%206y%20%2B%2042%20%3D%200)
![y(y - 7) - 6(y - 7) = 0](https://tex.z-dn.net/?f=y%28y%20-%207%29%20-%206%28y%20-%207%29%20%3D%200)
![(y - 6) (y - 7) = 0](https://tex.z-dn.net/?f=%28y%20-%206%29%20%28y%20-%207%29%20%3D%200)
Either; y-6 = 0
y = 6
Or;
y-7=0
y = 7
<em>Keeping the value of y as "7" in equation (ii)</em>
x*y = 42
7x = 42
X = 42/7
Therefore, the value of X is 6.
Therefore, either 1st friend is 6 years and 2nd is 7 years.
<em><u>H</u></em><em><u>o</u></em><em><u>p</u></em><em><u>e</u></em><em><u> </u></em><em><u>it </u></em><em><u>helps</u></em><em><u>.</u></em><em><u>.</u></em><em><u>.</u></em>
Answer:
True
Step-by-step explanation:
Type I and Type II are not independent of each other - as one increases, the other decreases.
However, increases in N cause both to decrease, since sampling error is reduced.
A small sample size might lead to frequent Type II errors, i.e. it could be that your (alternative) hypotheses are right, but because your sample is so small, you fail to reject the null even though you should.